Disney Frozen: Challenging the Traditional Gender Roles of Disney Princesses - Putri, Novia Ardellia (Universitas Negeri Surabaya, 2022)
Society's expectations of how we should act, speak, dress, take care of ourselves, and behave are known as gender roles. For instance, it is expected of girls and women in general to behave politely, be accommodating, and be caring. Men are typically thought to be powerful, aggressive, and brave. Gender expectations exist in every civilization, ethnic group, and culture, albeit they might differ greatly from group to group. They might alter over time even within the same society The 3D computer-animated musical fantasy movie Frozen was created in the United States and distributed by Walt Disney Pictures. The Hans Christian Andersen fairy tale